TRANSVERSALLY PROGRAMS EDUCATION UNDERGRADULATES IN PHYSICAL EDUCATION. Part 1: What is important is not a trained specialist, and developing professional - S. V. Dmitriev; E. V. Bystrickaja; D. I. Voronin (Вестник Мининского университета, 2017)
In article the transversal program of professional improvement of the undergraduate which is realized in sociocultural space of modern education is discussed. The terms framework of this sphere of knowledge didn’t settle yet therefore illimination of many guestions is expression of the author’s point of view.